Tinjauan Pengelolaan Jobs Description PMIK di Puskesmas Srondol - Sri Lestari; Meilinda Asrining Hapsari (Poltekkes Kemenkes Semarang, 2022)
Puskesmas in carrying out health services, one of its authorities is to carry out medical record management. Referring to Permenkes no. 55 of 2013 article 2 which states that the administration of medical records must be carried out by medical recorders. Medical Recorder is a person who has passed the Medical Record and Health Information education in accordance with the provisions of the legislation. The purpose of this research is to know the management of medical records, and health information as well as the staff for managing medical records at the Srondol Health Center. This type of research is descriptive qualitative with a case study approach. The results showed that the Srondol Health Center provided health services to BPJS patients and general patients. The patient naming system at the Srondol Health Center is adjusted to ID cards, family cards and other identity cards. Medical record management activities experienced several obstacles because they did not have officers with a medical record education background so that the transfer of medical record media from manual to electronic was constrained. The writing of patient names (Mr, Ny, Son, Br) is not standardized. Diagnostic coding is only known and carried out by doctors and midwives. The conclusion obtained is that the management of medical records and health information at the Srondol Health Center still found some things that were not in accordance with the regulations, so it was advisable to make adjustments to the medical record personnel regulations to improve their services.